Mesoporous Single‐Crystal Lithium Titanate Enabling Fast‐Charging Li‐Ion Batteries (Adv. Mater. 18/2022). Issue 18 (5th May 2022) - Jin, Xu; Han, Yehu; Zhang, Zhengfeng; Chen, Yawei; Li, Jianming; Yang, Tingting; Wang, Xiaoqi; Li, Wanxia; Han, Xiao; Wang, Zelin; Liu, Xiaodan; Jiao, Hang; et al.
Abstract : Mesoporous Materials In article number 2109356, Jianming Li, Pengfei Yan, Shuhong Jiao, and co‐workers report mesoporous single‐crystalline lithium titanate microrods featured with a single‐crystalline structure and interconnected pores inside for fast‐charging Li‐ion batteries (LIBs). The unique structure of lithium titanate enables a short lithium‐ion diffusion distance and fast penetration of electrolytes into the electrode interior during battery cycling, which contribute to high‐rate capability and excellent cycling stability. The novel design of porous single‐crystalline materials paves a new venue for developing fast‐charging materials for LIBs.